Synthesis of MDM2 Inhibitors to Reactivate p53 Function - Gohil, Chirag J. (International Journal of Pharmaceutical & Biological Archive, 2023)
Cancer is arise by inhibition of cell killing apoptosis process. Specific protein–protein interaction is responsible for the inhibition of apoptosis in the body. In this study, novel heterocyclic compounds (1,3,4-thiadiazole based) were synthesized. Synthesized compounds were successfully characterized by physical and spectral methods. And biological activity of the synthesized compounds was evaluated by cell-based assays. MTT assay was performed to determine the anti-neoplastic activity of the synthesized compounds. Moreover, a potency of the synthesized compounds was derived by IC50 value. In an assay (in vitro), the synthesized compound induced the apoptosis in the cancer cell line. Hence, it will be proven as a potential anticancer agent.